Advances of astaxanthin-based delivery systems for precision nutrition. (September 2022) - Chen, Yannan; Su, Wentao; Tie, Shanshan; Zhang, Lijuan; Tan, Mingqian
Abstract: Background: Astaxanthin is a marine carotenoid which has received widely attention due to its strongly functional activity in food industry. However, the poor water solubility and chemical instability restricts its bioavailability and antioxidation application. Thus, it is necessary to find effective method to protect astaxanthin against degradation and further exert its potential benefits in nutrition intervention. Scope and approach: The emphasis of this review is to highlight the construction of astaxanthin-based delivery systems, including lipid-based delivery systems and polymer-based delivery systems. Meanwhile, the potential benefits of encapsulating astaxanthin in terms of precision nutrition are summarized, which include promoting cellular uptake, intervening various disease, and achieving targeted delivery in cell or organelle levels. Finally, challenges and future perspectives of targeted astaxanthin for precision nutrition are further discussed. Key findings and conclusions: Well-designed astaxanthin-based delivery systems can enhance the stability of astaxanthin during food processing and in vivo digestion. Further improving its bioavailability through targeted delivery of astaxanthin-based products, especially for special populations, will meet the multiple needs of the public for food nutrition and health. Highlights: Remarkable technologies of developing astaxanthin delivery systems are elucidated. Current challenges to practical concerns for astaxanthin utilization are illustrated. Future developments of targeted astaxanthin for precision nutrition are discussed.